Menumbuhkan Fitrah Keimanan (Kajian Konsep Fitrah Based Education) - Muksal Mina Putra; Fidhia Andani; Jeni Fransiska; Putri Hairani (Insititut Agama Islam Negeri (IAIN) Curup, 2020)
This article aims to present the concept of fitrah faith and its development methods according to the study of fitrah based education integrated by Harry Santosa. This type of research is library research research that examines the text and analyzes it to be presented descriptively to gain meaning. The results showed that methods to cultivate faith fitrah according to the study of fitrah based education concept can be done by (1) building an atmosphere of keshalihan, and (2) exemplary. Building an atmosphere of piecy is meant to foster a positive image of the child about God, the Apostle, and Religion, so that the fitrah of his faith grows. While the motto of exemplary can be done by the technique of telling the exemplary stories of prophets, companions, the beauty of heaven and goodness.